Metodologia da problematização na integração dos conteúdos de fisiologia humana no ensino médio - Moi, Jaquilini Fátima (2019)
This study refers to an innovative initiative to implement the Problematization Methodology, according to the technique of the Maguerez Arc stages. The main objective of this work was to analyze the limits and possibilities of this proposal to encourage the assimilation of Human Physiology contents in High School. The field of study was the Military Police State School “Cabo PM Antônio Dilceu da Silva Amaral”, located in the Sorriso municipality (MT). The aim was to arouse the students' interest in the physiology content and, consequently, to make it easier to assimilate it through a reflective analysis of the problems that have been interfering with school productivity, so that the students can transform them and contribute with improvements in society. In a second moment, it was evaluated the learning of concepts in the classroom and the awakening of the criticality of these students for an action-reflection-action in the solution of the daily problems in which they are inserted. The method employed in this work was the focal group, a research method capable of simultaneously reflecting themes using the author's personal points of view, in order to approximate and correlate the facts, offering flexibility and adaptability in analysis for identification and results report. Having concluded the teaching and learning process, it could be stated that the Problematization Methodology, when applied according to the Maguerez Arc stages, may solve the most diverse problems that interfere with school productivity, allowing students a dynamic reflection on reality and the achievement of viable solutions in their social context.